PRATAL FLORA COMPONENTS IN PARKS OF POLTAVA CITY - Орлова, Л.Д. (World of Medicine and Biology, 2017)
The herbaceous component of the flowering ray flora of Poltava parks has practically not been studied. We have found that it includes 322 species, which relate to 216 genera, 54 families. In the presence of representatives of different types of meadow phytocenoses (landed, flood, and lowland) in the parks there is a tendency similar to the general characteristics of the meadow flora of parks in terms of the quantity of species Magnoliophyta. The largest variety of meadow species in the parks is found out of floodplain grasslands (80.0%), less - landed (50.3%) and lowland (40.3%) of the total number of identified representatives. The first place in the spectrum of flora families in the region, as in Most of the Holarctic flora, belongs to the Asteraceae family. High places (in the top ten) occupy such other leading families of flora of the Ancient Mediterranean: Fabaceae, Caryophyllaceae, Apiaceae, Lamiaceae, Rosaceae. The second, ninth and tenth places belong mainly to Holarctic families - Poaceae, Ranunculaceae, Cyperaceae. Third place was taken by representatives of the family Brassicaceae, which is an indicator of a significant rerralization of the territory. Among the revealed meadow representatives of the flora of Poltava parks are dominated by dicotyledonous species (the ratio of monocotyledons and dicotyledons is 1.0: 4.0). Percentage of representatives of dicotyledons was 80.0%, and monocots - 20.0%. The ratio of the diversity of species of dicotyledons and monocotyledonous representatives of flora parks from different types of onions was unequal. Thus, meadows from low-lying phytocoenoses had it at the level of 1.0: 3.0, floodplain - 1.0: 5.7, steadily - 1.0: 7.1. It is found out that in the ray of flora of the park only 22 genera contain three or more species, the rest have 1-2 representatives. The calculations confirm that there are 6.0 species for one family of floral flora of parks in Poltava, one species in total - 1.5 species.